Perampasan Aset Tanpa Pemidanaan Dalam Perspektif Economic Analysis Of Law - Irwan Hafid (Lex Renaissance, 2021)
Indonesia currently does not explicitly regulate the seizure of assets without punishment in Indonesian laws and regulations. Existing regulations only regulate the seizure of assets through criminal proceedings. This study wants to examine how the urgency of regulating the concept of non-conviction based asset forfeiture in the legislation and its correlation to the return of state finances in the perspective of economic analysis of law. This research is normative juridical, that is carried out by reviewing or analyzing secondary data in the form of legal materials, especially primary legal materials, secondary legal materials, and tertiary legal materials. The results of this study concluded that the regulation on asset confiscation without punishment is still not comprehensive enough so that the ratification of the Asset Confiscation Bill is needed. In the perspective of economic analysis of the law, the ratification of the bill can minimize the number of perpetrators of hiding assets and the efficiency of law enforcement policy efforts, so that it can be oriented towards the effectiveness of recovering state financial losses.Key words: Economics; seizure of assets; criminal; legalAbstrakIndonesia saat ini tidak secara tegas mengatur perampasan aset tanpa pemidanaan dalam peraturan perundang-undangan di Indonesia. Regulasi yang ada hanya mengatur perampasan aset melalui proses pidana. Penelitian ini ingin mengkaji bagaimana urgensi pengaturan konsep perampasan aset tanpa pemidanaan (non-conviction based asset forfeiture) dalam peraturan perundang-undangan serta korelasinya terhadap pengembalian keuangan negara dalam perspektif analisa ekonomi terhadap hukum (economic analysis of law). Penelitian ini bersifat yuridis normatif, yakni dilakukan dengan cara mengkaji atau menganalisis data sekunder yang berupa bahan hukum terutama bahan hukum primer, bahan hukum sekunder, dan bahan hukum tersier. Hasil penelitian ini menyimpulkan bahwa pengaturan tentang perampasan aset tanpa pemidanaan masih belum cukup komprehensif sehingga dibutuhkan pengesahan RUU Perampasan Aset. Dalam perspektif analisa ekonomi terhadap hukum, pengesahan RUU tersebut dapat menimimalisir tingginya pelaku kejahatan penyembunyian aset dan efisiensi upaya kebijakan penegakan hukum, sehingga dapat berorientasi pada efektivitas pengembalian kerugian keuangan negara.Kata Kunci: Ekonomi; perampasan aset; pidana; hukum